Identification of disinfection by-products in freshwater and seawater swimming pools and evaluation of genotoxicity. (March 2016) - Manasfi, Tarek; De Méo, Michel; Coulomb, Bruno; Di Giorgio, Carole; Boudenne, Jean-Luc
Abstract: Exposure to disinfection byproducts (DBPs) in swimming pools has been linked to adverse health effects. Numerous DBPs that occur in swimming pools are genotoxic and carcinogenic. This toxicity is of a greater concern in the case of brominated DBPs that have been shown to have substantially greater toxicities than their chlorinated analogs. In chlorinated seawater swimming pools, brominated DBPs are formed due to the high content of bromide. Nevertheless, very little data is reported about DBP occurrence and mutagenicity of water in these pools. In the present study, three seawater and one freshwater swimming pools located in Southeastern France were investigated to determine qualitatively and quantitatively their DBP contents. An evaluation of the genotoxic properties of water samples of the freshwater pool and a seawater pool was conducted through the Salmonella assay (Ames test). The predominant DBPs identified in the freshwater pool were chlorinated species and included trichloroacetic acid, chloral hydrate, dichloroacetonitrile, 1, 1, 1-trichloropropanone and chloroform. In the seawater pools, brominated DBPs were the predominant species and included dibromoacetic acid, bromoform and dibromoacetonitile. Bromal hydrate levels were also reported. In both types of pools, haloacetic acids were the most prevalent chemical class among the analyzed DBP classes. The distribution of other DBP classes varied depending on the type of pool. As to genotoxicity, the results of Ames test showed higher mutagenicity in the freshwater pool as a consequence of its considerably higher DBP contents in comparison to the tested seawater pool. Highlights: A freshwater and three seawater swimming pools located in France were investigated. Trihalomethanes, haloacetic acids, haloacetonitriles and other DBPs were measured. Predominance of brominated DBPs in seawater vs. chlorinated ones in freshwater pool The freshwater pool exhibited more mutagenic potency than the tested seawater pool. The higher mutagenicity of the freshwater pool is related to its higher DBP content.